Estado, pobreza e desigualdade de gênero: uma análise do lugar da mulher nas políticas públicas de transferência de renda - Forte, Elaina Cavalcante (2022)
This research investigates the role of the State in the fight against poverty with a focus on public policies and from a feminist perspective. Its specific research object are the income transfer policies wit h conditionalities as the main State action aimed at fighting intergenerational poverty, since it is the most preferred in the field of social assistance in the countries of the global South. It is based on the feminist and intersectional theoretical frame work to analyze the implications of these programs for the situation of women and their effects on gender equity. As a case study, we chose to analyze the “Bolsa Família” Program, which completed 18 years of existence in 2021 and, at the same time, was ter minated by a decree and was replaced by the “Auxílio Brasil” Program. We focused on the evolution of the conception of the State, the scientific treatment of poverty, the dimensions of inequality and vulnerability, the effects of the pandemic on women and girls, and the scenario of the replacement of the “Bolsa Família” Program. It adopts a methodology the document analysis so that our sources were the legislation and the official databases of governmental bodies and agencies (PNAD, IBGE, IPEA, UN), as well as studies undertaken by research groups from federal universities (UFC, USP). As challenges and limitations, we had the inexistence of updated public data, since the IBGE Census was postponed to the second semester of 2022 (August), after the completion of this research. We conclude that, despite being essentially feminized programs, the gender approach is absent in their design, which ends up “functionalizing” women in the domestic and caregiving roles, with more unequal effects for black women. Despite that, such programs are not totally indifferent to improvements in relation to their autonomy and empowerment, being important in reducing poverty and improving nutritional quality, education, and health indicators. We also concluded that it is necessary t o complement these programs with other public policies aimed at recognizing women as desirable beings, enabling them to play distinct roles in the public sphere. To achieve that goal, it is essential to reorient social protection policies with a gender int ersectional aspect, taking into consideration indicators of empowerment , valorization of (re)productive work and possibilities in the formal labor market to achieve a better wellbeing and equality for both men and women.